Hydrothermal performance improvement of an inserted double pipe heat exchanger with Ionanofluid - Das, L. (Elsevier Ltd, 2021)
To meet the growing energy demand, double pipe heat exchangers (DPHEX), which are used in a variety of energy and thermal engineering applications, require improved heat transfer performance. In this study, a new class of surfactant-free Ionanofluid is formulated at three different concentrations of 0.01, 0.05 and 0.10 wt and thermophysical and rheological properties are assessed. Zeta potential analysis is executed to assess the dispersion stability. An optimum concentration has been selected to investigate the hydrothermal performance of an insert fitted DPHEX at varying Re from 400 to 2000. The conventional twisted tape (TT) insert is modified by introducing different types of geometrical (triangular, rectangular, and circular) cuts on its surface. According to the Ionanofluid characterization, 0.10 wt Ionanofluid has the highest thermal conductivity enhancement of 64 and heat capacity of 16.1 when compared to the base fluid, with a maximum enhancement in Nu of about 116â136 at varying Re. The rectangular-cut TT imparts highest heat transfer enhancement as the additional vortices is more intensive than other cut-inserts. Nevertheless, the value of PEC for the combination of Ionanofluid and RCTT insert, remaining between 1.61 and 1.68 over the entire range of Re, is greater than other combinations. Â© 2021